Multicentre individual randomised controlled trial of screening and brief alcohol intervention to prevent risky drinking in young people aged 14–15 in a high school setting (SIPS JR-HIGH): study protocol. Issue 12 (23rd December 2016) - Giles, Emma L; Coulton, Simon; Deluca, Paolo; Drummond, Colin; Howel, Denise; Kaner, Eileen; McColl, Elaine; McGovern, Ruth; Scott, Stephanie; Stamp, Elaine; Sumnall, Harry; Tate, Les; et al.
Abstract : Introduction: Drinking has adverse impacts on health, well-being, education and social outcomes for adolescents. Adolescents in England are among the heaviest drinkers in Europe. Recently, the proportion of adolescents who drink alcohol has fallen, although consumption among those who do drink has actually increased. This trial seeks to investigate how effective and efficient an alcohol brief intervention is with 11–15 years olds to encourage lower alcohol consumption. Methods and analysis: This is an individually randomised two-armed trial incorporating a control arm of usual school-based practice and a leaflet on a healthy lifestyle (excl. alcohol), and an intervention arm that combines usual practice with a 30 min brief intervention delivered by school learning mentors and a leaflet on alcohol. At least 30 schools will be recruited from four regions in England (North East, North West, London, Kent and Medway) to follow-up 235 per arm. The primary outcome is total alcohol consumed in the last 28 days, using the 28 day Timeline Follow Back questionnaire measured at the 12-month follow-up. The analysis of the intervention will consider effectiveness and cost-effectiveness. A qualitative study will explore, via 1:1 in-depth interviews with (n=80) parents, young people and school staff, intervention experience, intervention fidelity and acceptability issues, using thematic narrative synthesis to report qualitative data. Ethics and dissemination: Ethical approval was granted by Teesside University. Dissemination plans include academic publications, conference presentations, disseminating to local and national education departments and the wider public health community, including via Fuse, and engaging with school staff and young people to comment on whether and how the project can be improved. Trial registration trial: ISRCTN45691494 ; Pre-results.